2022
DOI: 10.3989/gya.0110211
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of red mombin seed oil (Spondias purpurea L.): phenolic profile, fatty acid profile and chemical characterization of the cake, residue from the oil extraction

Abstract: The ultrasound-assisted method was used to extract oil from the red mombin seed, mainly aiming to analyze yield. A multivariate analysis served to define optimized parameters (6.46 minutes and S/S ratio of 1:23.10 mass:volume) for ultrasound-assisted extraction (UAE) with the objective of maximizing yield, using the response surface methodology (RSM) and desirability graph with central variables and axial points determined by the central composite rotatable design (CCRD). In addition to the optimization of oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…7,10 Several studies have been carried out on the recovery, bioconversion, recycling and use of bioactive compounds from fruit residues. 8,[11][12][13][14][15][16] In this context, the extraction of bioactive compounds present in the ciriguela residue could increase the commercial value of the raw material and the profitability of fruit processing. Several studies have evaluated the recovery of phenolic compounds from fruit skin and seeds by different extraction methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 Several studies have been carried out on the recovery, bioconversion, recycling and use of bioactive compounds from fruit residues. 8,[11][12][13][14][15][16] In this context, the extraction of bioactive compounds present in the ciriguela residue could increase the commercial value of the raw material and the profitability of fruit processing. Several studies have evaluated the recovery of phenolic compounds from fruit skin and seeds by different extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Currenly, with the availability of modern technologies, together with the principles of ‘Green Chemistry’, new concepts have been established, leading to the effective use of waste and by‐products from the agri‐food sector for the production of value‐added products 7,10 . Several studies have been carried out on the recovery, bioconversion, recycling and use of bioactive compounds from fruit residues 8,11‐16 …”
Section: Introductionmentioning
confidence: 99%
“…RSM cannot only determine the interactions between processing factors, but also reduces the number of experimental trials, development time, and overall cost [ 15 ]. The successful application of RSM to optimize the UAE process to obtain edible oils from plant tissues, such as hemp seeds [ 16 ], Moringa oleifera leaves [ 17 ], Moringa Peregrina seeds [ 18 ], fresh aerial parts of Angelica Keiskei Koidzumi [ 19 ], and red mombin seeds ( Spondias purpurea L.) [ 20 ], has been recently performed. In addition, Susanti et al have recently reported that using the UAE process under the optimal conditions determined by RSM is an efficient method to substitute the conventional technique for the simultaneous extraction of oil and phenolic compounds from red fruit ( Pandanus conoideus ) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%